Epipactis muelleri Godfery (Orchidaceae), a new species for the flora of Ukraine - Fateryga, V.V.; Kreutz, C.A.J.; Fateryga, A.V.; Reinhardt, J. (Український ботанічний журнал, 2013)
A self-pollinated orchid, Epipactis muelleri Godfery, is reported from the Crimea as a new species for the flora of Ukraine. Data on key diagnostic characters of the species and collected herbarium specimens are provided.